2006
DOI: 10.1093/jn/136.4.913
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fibers Affect Viscosity of Solutions and Simulated Human Gastric and Small Intestinal Digesta

Abstract: Two experiments were conducted to determine the viscosities of both soluble and insoluble dietary fibers. In Expt. 1, corn bran, defatted rice bran, guar gum, gum xanthan, oat bran, psyllium, soy hulls, stabilized rice bran, wheat bran, wood cellulose, and 2 methylcellulose controls (Ticacel 42, Ticacel 43) were hydrated in water overnight at 0.5, 1, 1.5, or 2% concentrations. In Expt. 2, guar gum, oat bran, psyllium, rice bran, wheat bran, and wood cellulose were subjected to a 2-stage in vitro gastric and sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
118
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(126 citation statements)
references
References 14 publications
4
118
0
4
Order By: Relevance
“…They are not digested by human pancreatic or brush border enzymes and therefore are not expected to be fully absorbed. However, their consumption does help to control blood glucose levels and lipid concentrations by enhancing the viscosity of the gastrointestinal contents [46].…”
Section: Nutritional Values Of Rice By-productsmentioning
confidence: 99%
“…They are not digested by human pancreatic or brush border enzymes and therefore are not expected to be fully absorbed. However, their consumption does help to control blood glucose levels and lipid concentrations by enhancing the viscosity of the gastrointestinal contents [46].…”
Section: Nutritional Values Of Rice By-productsmentioning
confidence: 99%
“…Chylomicron plays a role to the transfer of lipids absorbed in the small intestine into the liver. Some water-soluble dietary fibers, such as guar gum, exhibit a highly viscous character in the human gastrointestinal tract 19) . Furthermore, it has been reported that the ingestion of guar gum markedly reduces blood glucose levels and improves insulin sensitivity in STZ diabetic rats 20) , and induces a lipid-lowering effect in cholesterol-fed rats 21) .…”
mentioning
confidence: 99%
“…Bladder and bowel conditions, intestinal colic and bedwetting have all been helped by soaking in a bath of Oat Straw. These effects of oat β-glucan were well reviewed by Mälkki and Virtanen (2001), Ulmius et al (2011), Wang et al (2002 and Dikeman et al (2006).…”
Section: Other Benefitsmentioning
confidence: 86%